1995
DOI: 10.1021/bi00044a014
|View full text |Cite
|
Sign up to set email alerts
|

Human Aldose Reductase: pK of Tyrosine 48 Reveals the Preferred Ionization State for Catalysis and Inhibition

Abstract: Detailed analyses of the pH variation of kinetic parameters for the forward aldehyde reduction and reverse alcohol oxidation reactions mediated by recombinant human aldose reductase, for inhibitor binding, and for kinetic isotope effects on aldehyde reduction have revealed that the pK value for the active site acid-base catalyst group Tyr48 is quite sensitive to the oxidation state of the bound nucleotide (NADPH or NADP+) and to the presence or absence of the Cys298 sulfhydryl moiety. Thus, the Tyr48 residue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 31 publications
7
66
0
1
Order By: Relevance
“…Results of pH studies revealed a kinetically unperturbed pK a of 8.50 for the AKR2B5-NADH complex above which the reductase activity was lost (32,34). The ionizable group of AKR2B5 to which the pK a of 8.50 can be assigned is most probably Tyr-51, consistent with pK ato-group assignments in other AKRs, particularly aldose reductase (16,18,33). Interestingly, the same pK a was observed in the pH profile of log k cat /K for a Asp-46!Asn Lys-80!Ala double mutant of AKR2B5 which was designed to substitute the side chain of Lys-80 without altering the overall net charge of the active site (34).…”
Section: Acid/base Catalysis -Tyr-51supporting
confidence: 62%
“…Results of pH studies revealed a kinetically unperturbed pK a of 8.50 for the AKR2B5-NADH complex above which the reductase activity was lost (32,34). The ionizable group of AKR2B5 to which the pK a of 8.50 can be assigned is most probably Tyr-51, consistent with pK ato-group assignments in other AKRs, particularly aldose reductase (16,18,33). Interestingly, the same pK a was observed in the pH profile of log k cat /K for a Asp-46!Asn Lys-80!Ala double mutant of AKR2B5 which was designed to substitute the side chain of Lys-80 without altering the overall net charge of the active site (34).…”
Section: Acid/base Catalysis -Tyr-51supporting
confidence: 62%
“…The polyol pathway enzyme aldose reductase catalyzes the reduction of aldo sugars and other saturated and unsaturated aldehydes [16][17][18][19][20]. This enzyme constitutes the first and the rate limiting step of the polyol pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds (III and V) well occupied in the receptor cavity and forms hydrogen bonds and hydrophobic interactions (Figures 4 and 5). The sulfonamide group of III and V is anchored into the anion-binding site formed by Ala299, Leu300 and Trp111 and forms hydrogen-bonding with Trp111, which is key residue in binding and catalysis 32,33 . The 1,2,3,4-tetrahydronaphthalene ring core gets tightly trapped in the hydrophobic pocket formed by Phe122, Leu300, Leu301, Leu124 and Val130.…”
Section: Dockingmentioning
confidence: 99%
“…It has been shown that there is an approximately 85% sequence similarity between rat lens and human aldose reductase (ALR2), while the proposed active sites of both enzymes are identical 32 . The performed assay was based on a spectrometric measurement, which is proven to be a reliable method 33 , with DL-glyceraldehyde as the substrate and NADPH as the cofactor. Quercetin, a known ARI was used as a positive control.…”
Section: Aldose Reductase Inhibitionmentioning
confidence: 99%